2020
DOI: 10.5588/pha.20.0004
|View full text |Cite
|
Sign up to set email alerts
|

Impact and operational feasibility of TrueNat MTB/Rif under India’s RNTCP

Abstract: Background: The Revised National Tuberculosis Control Programme (RNTCP) in Andhra Pradesh, India, introduced TrueNat™ MTB/Rif, a rapid molecular test for detecting Mycobacterium tuberculosis (MTB) and rifampicin (RIF) resistance at 193 TB units (TUs) in October 2018. We evaluated its impact on TB diagnosis and assessed the operational feasibility of its deployment at point-of-care (POC) settings.Methods: We compared the number of presumptive TB cases tested and the number (proportion) of microbiologically pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
11
1
Order By: Relevance
“…Further, 70% of the technical staff reported it to be similar or technically less demanding than Xpert. 41 In contrast to these two assays, the cost per It is important to note that although TruPlus fared well in diagnosing GITB in the current study, its negative predictive value was substantially low (69% in the current study). This means that TruPlus, just like Xpert, can only be used for ruling-in GITB, but a negative result cannot rule-out GITB.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Further, 70% of the technical staff reported it to be similar or technically less demanding than Xpert. 41 In contrast to these two assays, the cost per It is important to note that although TruPlus fared well in diagnosing GITB in the current study, its negative predictive value was substantially low (69% in the current study). This means that TruPlus, just like Xpert, can only be used for ruling-in GITB, but a negative result cannot rule-out GITB.…”
Section: Discussioncontrasting
confidence: 55%
“…In a cost–benefit analysis by Lee et al ., 42 Truenat was found to have improved linkage‐to‐care and was cost‐effective in the public sector health care of India as a point‐of‐care test. Further, 70% of the technical staff reported it to be similar or technically less demanding than Xpert 41 . In contrast to these two assays, the cost per sample for MPCR was observed to be much cheaper ($10) in the present study; however, it is limited to detection of M. tuberculosis only, without rifampicin susceptibility and requires more hands‐on techniques.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In addition, it is not uncommon for nondeterminate results to be higher than normal when a new system is introduced, with improvements seen as operators gain experience with the systems. A recent study found technicians reporting comfort with assay operations after a median of 10 tests, with an associate reduction in invalid test results [ 26 ]. In terms of patient-important outcomes, quicker turnaround from testing to treatment can be expected when testing is conducted at primary healthcare centres.…”
Section: Discussionmentioning
confidence: 99%